Five golden wings - Andrews, Donna (Andrews, Donna. Meg Langslow mysteries, 2025)
"Readers will flock to NYT bestselling author Donna Andrews' latest installment in the award-winning Meg Langslow series. Two of Meg's cousins, members of Mother's vast Hollingsworth clan, are getting married, and both have chosen Caerphilly for their Christmas destination wedding . . on the same day, in the same venues. But while they're cousins they're also lifelong enemies. Mother's efforts to keep the peace are wearing her down, and the battling brides (and their mothers) are making the holiday season miserable for everyone. So Meg steps in to keep the peace. And it was going badly even before she stumbles over the murdered body of the wedding photographer. Unfortunately, there are plenty of suspects. The photographer has been hitting on many of the guests, bridesmaids . . . possibly even one or both of the brides. He's also been slinking about and taking candid shots that are unflattering, embarrassing . . . occasionally even incriminating. Can Meg help the local police nab the killer in time for the weddings to go on as planned? Unless, of course, the killer was one of the brides or grooms, in which case she needs to identify the killer in time to reveal their identity when she hears those fateful words, "If any of you can show just cause why they may not lawfully be married, speak now; or else forever hold your peace.""-- Provided by publisher.